Architecturally speaking : practices of art, architecture, and the everyday - Read, Alan, 1956- (Routledge, 2000)
Architecturally Speaking is an international collection of essays by leading architects, artists and theorists of locality and space. This book will appeal to urbanists, geographers, artists, architects and cultural historians.